A, The Perbandingan Fonologi Bahasa Melayu Isolek Desa Pulau Air Raja Kecamatan Galang dengan Desa Pulau Mengkadah Kecamatam Bulang Kota Batam: Perbandingan Fonologi Bahasa Melayu Isolek Desa Pulau Air Raja Kecamatan Galang dengan Desa Pulau Mengkadah Kecamatam Bulang Kota Batam - Reski (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses comparative phonology which focuses on changes in vowel phonemes and consonant phonemes. This is motivated by differences in the pronunciation of language sounds but they have the same meaning by the people of Pulau Air Raja Village, Galang District and Pulau Mengkadah Village, Bulang District, Batam City. The approach and type of research used is descriptive qualitative. The data collection technique for this research is a conversational involvement technique. Based on the results of data collection obtained in the field, in this study there were forty-nine words that had a comparison of vowel phoneme to vowel phoneme, two comparisons of consonant phoneme to vowel phoneme, four comparisons of consonant phoneme to consonant phoneme, and one comparison of vowel phoneme to phoneme. consonant. Of the fifty-six words in the comparison of the two languages, the form of pronunciation is that the people of Pulau Air Raja Village, Galang District, are more dominant in using the vowel phoneme /∂/, while the people of Mengkadah Island, Bulang District are more dominant in using the vowel phoneme /o/. The comparison of pronunciation in these two areas is due to the migration factor, because there are many new immigrants who occupy Air Raja Village and stay, so there are slight changes in pronunciation which results in differences in word pronunciation with Pulau Mengkadah Village, while the people of Pulau Mengkadah Village are local residents.